Usability in web-based online public access catalogs desgining human - centered library information systems - Luna, Joselino Emmanuel R. (2011)
Through the five (5) aspects of usability, enhancement and modifications were applied to creation of an OPAC prototype (Aklatan). The prototype was based from the current OPAC (iLib) and Information Retrieval (IR) systems available on the Internet.